ETHANOL EXTRACTION DESALINATION TEST USING PRE-TREATED MINE WASTEWATER CONCENTRATED BY REVERSE OSMOSIS - VÁSQUEZ SALAZAR, EDGAR E. (2024)
THIS ARTICLE INVESTIGATES THE EFFICIENCY OF USING ETHANOL AS THE EXTRACTING SOLVENT FOR THE DESALINATION OF PRE-TREATED MINE WASTEWATER. THE WASTEWATER, CONCENTRATED THROUGH REVERSE OSMOSIS (RO), HAD A SALINITY OF 47,115.60 PPM BEFORE SOLVENT EXTRACTION. RESULTS SHOWED THAT 13.31% OF THE SALT WAS EXTRACTED VIA ETHANOL EXTRACTION USING A RATIO OF 85:15 (V/V) ETHANOL TO RO CONCENTRATE AT 55 °C. AN AVERAGE SALINITY REDUCTION OF 46.04% WAS ACHIEVED. ETHANOL WAS EFFECTIVE IN REDUCING SCALING IONS SUCH AS CALCIUM AND SULFATE AND, TO A LESSER EXTENT, MAGNESIUM. THE HIGHEST REMOVAL EFFICIENCIES WERE ACHIEVED FOR THE ARSENIC AND MANGANESE ELEMENTS, DESPITE THEIR LOW INLET CONCENTRATIONS (0.299 PPM AND 0.181 PPM, RESPECTIVELY). THE REMOVAL EFFICIENCIES OF MONOVALENT IONS WERE MODERATE. HOWEVER, THE RESULTS REVEALED CONCERNING LEVELS OF IRON, LITHIUM, AND BORON, SHOWING A HIGH CONCENTRATION OF THE TWO LAST ELEMENTS IN THE PRODUCT WATER. THIS STUDY SHOWS THE SIGNIFICANCE OF ETHANOL EXTRACTION DESALINATION AS A VIABLE ALTERNATIVE TO THERMAL DESALINATION PROCESSES, ESPECIALLY FOR GENERATING WATER THAT MEETS SPECIFIC END-USE NEEDS. © 2024 THE AUTHOR(S)